Impact of The Covid-19 Pandemic on Profitability of Companies Incorporated in IDX30 (Studies Before and During the Pandemic Took Place) - Putri Ekawati Darma; Muhsin N Bailusy; Irfandi Buamonabot (AIBPM Publisher, 2022)
This study retested the hypothesis of previous research by Evany et al., (2022) so that this type of research is confirmatory. The hypothesis proposed is whether there is a significant difference in profitability ratios in companies incorporated in IDX30 before and during the pandemic. Quantitative data analysis uses secondary data in the form of financial statements during the two-year research period. Data can be obtained from the Indonesia Stock Exchange or www.idx.co.id. Based on these data, there are as many as 30 companies, but those that meet the sample criteria are only 18 companies and obtained as many as 108 data for three research variables. With the help of SPSS 25 software using wilcoxon sign rank non-parametric tests, the results showed that there was a significant difference in the period before the pandemic and at the time of the pandemic occurred only in the ROA ratio, while in the ROE and NPM ratios the results were no significant differences.